Analysis of the current status of intelligent system "Internet of Things" and trends in the development - Goriushkina, Alla; Korolev, Roman (НТУ "ХПІ", 2017)
The subject of study in the article is the processes of analysis and evaluation of attack intelligent systems "Internet of Things" (IoT). The goal is to reduce the potential attacks due to the risks of intellectual functioning of the IoT systems, through the timely adoption of security measures. Objectives: the classification of attacks on all levels of intelligent systems, IoT, highlighting the main factors and their causes; the following results are obtained. The analysis of the current state of intelligent systems, IoT, analyzed all levels of functioning, and classification of hackers on the factors of their occurrence. The negative consequences negatively affecting the basic characteristics of the functioning of the IoT systems. As a result, a block diagram of attacks at all levels of the IoT. Conclusions. The article analyzes the current state of intelligent systems "Internet of Things" (IoT). It is shown that a significant increase in computer network devices connected to the network creates new opportunities for the development of modern society in the field of science and technology. However, the significant development of "Internet of Things" is directly proportional to increases the possibility of attacks in computer networks. Therefore, the scientific direction improvement of existing or development of new algorithms, models, and their implementation to ensure major safety criteria for IoT are relevant.

Предметом вивчення в статті є процеси аналізу та оцінки атак інтелектуальної системи "Internet of Things" (IoT). Мета – зниження потенційних атак, зумовлених ризиками функціонування інтелектуальної системи IoT, шляхом своєчасного вжиття заходів безпеки. Завдання: класифікація атак на всіх рівнях інтелектуальної системи IoT з виділенням основних факторів і причин їх виникнення; Отримані наступні результати. Проведено аналіз сучасного стану інтелектуальної системи IoT, проаналізовано всі рівні функціонування та класифікацію атак хакерів за факторами їх виникнення. Визначено негативні наслідки, що негативно впливають на основні характеристики функціонування IoT. В результаті сформована структурна схема атак на всіх рівнях IoT. Висновки. У статті аналізується поточний стан інтелектуальної системи "Internet of Things". Показано, що значне зростання комп'ютерних мережевих пристроїв, підключених до мережі створює нові можливості для розвитку сучасного суспільства в галузі науки і техніки. Однак, значний розвиток "Internet of Things" прямо пропорційно збільшує можливість атак в комп'ютерній мережі. Тому наукові напрямки вдосконалення існуючих або розробка нових алгоритмів, моделей та їх реалізації для забезпечення основних критеріїв безпеки для IoT є актуальними.
Аналіз сучасного стану інтелектуальної системи "Internet of Things" та тенденції її розвитку
Keywords: intelligent systems Internet of Things; attacks; security; computer technology; інтелектуальна система "Internet of Things"; атаки; безпека; комп'ютерні технології